LGG-51. METABOLIC PROFILING IN PEDIATRIC LOW GRADE GLIOMA IDENTIFIES GLUTATHIONE DEPLETION AFTER MTORC1 INHIBITION AND VALIDATES EVEROLIMUS AND CARBOPLATIN AS A POTENTIAL COMBINATION THERAPY. Issue 2 (22nd June 2018) - Poore, Brad; Yuan, Ming; Arnold, Antje; Price, Antionette; Alt, Jesse; Rubens, Jeffrey; Slusher, Barbara; Eberhart, Charles; Raabe, Eric
Abstract: The mTOR pathway contributes to the tumorigenicity of aggressive pediatric low grade glioma (pLGG) and TORC1 inhibitors have demonstrated efficacy in treating pLGG cell lines. The FDA-approved TORC1 inhibitor, everolimus, is currently in clinical trials for patients with recurrent/refractory pLGG. We hypothesized that metabolic alterations downstream of TORC1 inhibition could be targeted to synergize with everolimus and reduce pLGG tumorigenicity. We identified through unbiased metabolic screens and stable isotope tracing that glutathione was downregulated (p<0.001) after everolimus treatment in both in vitro and in vivo models of pLGGs. Based on this finding, we combined everolimus with carboplatin, a DNA damaging agent that is detoxified by glutathione conjugation. We treated 5 pLGG models (4 cell lines and one patient-derived xenograft) representing a range of mutations commonly found in pLGG including, BRAF-KIAA1549 fusion, BRAFV600E, and NF1 loss. To our knowledge, this study is the first to use a pLGG NF1 null cell line, JHH-NF1-PA1. Carboplatin synergized with everolimus to slow cell growth in most cell lines (CI<1 at Fa 0.5). The combination increased expression of apoptotic markers, (cleaved-PARP, cleaved caspase-3) and markers of DNA damage (phosphorylation of gamma-H2AX, 154%-1800% increase compared to carboplatin alone). The combination of carboplatin and everolimus reduced BRAFV600E-driven BT40 pLGG xenograft tumor growth better than either agent alone, (p<0.001 by ANOVA). Exogenous glutathione rescued the effects of everolimus, further supporting the mechanism of synergy between these agents. In summary, this study provides the pre-clinical justification for combining everolimus with carboplatin in pLGG clinical trials.